REORIENTASI HUKUM POLIGAMI: KAJIAN METODOLOGI DAN WACANA KEILMUAN NASR HAMED ABU ZAID - Arofik, Slamet; Imam Annas Mushlihin (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
This study examines the patterns of thought, methodology, and scholarly discourse of Nasr Hamid Abu Zayd, a contemporary Islamic thinker known for promoting a hermeneutical approach to Qur’anic studies. The research focuses on analyzing Abu Zayd’s concept of the relationship between text, context, and reader in interpreting the Qur’an historically and dynamically, particularly regarding the issue of polygamy. Employing a qualitative approach and literature analysis method, the study explores how Abu Zayd emphasizes understanding the Qur’an as a cultural product (manhaj al-thaqāfī), requiring interpretation that considers its social, historical, and political contexts. The study also highlights his critique of traditional approaches, which he views as insufficiently responsive to modern developments. The findings reveal that Abu Zayd’s methodology allows for an inclusive and progressive reading of the Qur’an, though it remains controversial among scholars. The study concludes that, according to Abu Zayd’s interpretation, polygamy is not permissible.